A Comprehensive Understanding of the Genomic Bone Tumor Landscape: A Multicenter Prospective Study - Xie, Xianbiao; Bian, Yiying; Li, Haomiao; Yin, Junqiang; Tian, Lantian; Jiang, Renbing; Zeng, Ziliang; Shi, Xiaoliang; Lei, Zixiong; Hou, Changhe; Qu, Yueting; Wang, Liwei; et al. (Frontiers in Oncology, 2022)
The complexity and heterogeneity increases the difficulty of diagnosis and treatment of bone tumor. We aimed to identify the mutational characterization and potential biomarkers of bone tumor. In this study, a total of 357 bone tumor patients were collected and the NGS-based YuanSu S panel which includes both DNA and RNA detection was performed for genomic alteration identification. The most common mutated genes in bone tumors include TP53, NCOR1, VEGFA, RB1, CCND3, CDKN2A, GID4, CCNE1, TERT, and MAP2K4. The amplification of genes such as NCOR1, VEGFA, and CCND3 were mainly occurred in osteosarcoma. Germline mutations analysis reveal a high frequency of HRD related mutations (46.4%, 13/28) in this cohort. With the assistance of RNA detection, 16.8% (19/113) gene fusions were independently detected in 20% (16/79) patients. Nearly 34.2% of patients harbor actionable targeted mutations, of which the most common mutation is CDKN2A deletion. The different mutational characterization between juvenile patient and adult patient indicated the potential effect of age in bone tumor treatment. According to the genomic alterations, the diagnosis of 26 (7.28%) bone tumors were corrected. The most easily misdiagnosed bone tumor include malignant giant cell tumor of bone (2.8%, 10/357) and fibrous dysplasia of bone (1.7%, 6/357). Meanwhile, we found that the mutations of MUC16 may be a potential biomarker for the diagnosis of mesenchymal chondrosarcomas. Our results indicated that RNA detection effectively complements DNA detection and increased the detection of gene fusions, and supported that NGS technology can effectively assist the diagnosis of bone tumors.